Two new species of Philosepedon Eaton (Diptera, Psychodidae, Psychodinae) from Europe, with comments on subgeneric classification - Omelková, Markéta; Ježek, Jan (Zootaxa, 2012)
A list of world species for subgenera of Philosepedon Eaton, including Philosepedon s. str., Trichosepedon Krek, and Philo-threticus Krek is given, and the subgenus Bahisepedon subgen. nov. is proposed to include some western hemisphere species.Philosepedon wagneri nom. nov. is proposed to replace P. orientale Wagner, a homonym of P. orientale Krek. Two new spe-cies from Europe, Philosepedon dumosum sp. nov. and P. perdecorum sp. nov., are described, and all important male diagnostic characters are discussed. The number of moth fly species known to occur in the Czech Republic is increased to 172.